2020
DOI: 10.3390/polym12061351
|View full text |Cite
|
Sign up to set email alerts
|

Sulfonation and Characterization of Tert-Butyl Styrene/Styrene/Isoprene Copolymer and Polypropylene Blends for Blood Compatibility Applications

Abstract: Hydrogenated styrenic block copolymers (HSBCs) have been used in medical tubing for many years due to their high clarity, flexibility, kink resistance, and toughness. However, when it comes to blood storage applications, HSBC compounds’ market has been limited because of their high hydrophobicity, which may trigger platelet adhesion when contacting with blood. HSBC needs to be physically or chemically modified in advance to make it blood compatible; however, HSBC has strong UV/ozone resistance, thermooxidative… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 30 publications
0
2
0
Order By: Relevance
“…Along with triazole fragments, negatively charged sulfonate groups are introduced into macromolecules, which contribute to an increase in the number of coordination centers of metal nanoparticles and a significant increase in the stabilizing ability of the copolymer. At the same time, the spectrum of useful properties of the polymer matrix is expanding, since it is known that blood-compatible drug carriers, which reduce protein absorption and platelet adhesion, as well as drug delivery systems have been developed on the basis of polyvinyl sulfonic acid [34][35][36][37][38][39][40].…”
Section: Introductionmentioning
confidence: 99%
“…Along with triazole fragments, negatively charged sulfonate groups are introduced into macromolecules, which contribute to an increase in the number of coordination centers of metal nanoparticles and a significant increase in the stabilizing ability of the copolymer. At the same time, the spectrum of useful properties of the polymer matrix is expanding, since it is known that blood-compatible drug carriers, which reduce protein absorption and platelet adhesion, as well as drug delivery systems have been developed on the basis of polyvinyl sulfonic acid [34][35][36][37][38][39][40].…”
Section: Introductionmentioning
confidence: 99%
“…In our previous work, we found that the sulfonation of blends of polypropylene/ tert -butyl SEPS demonstrated physical stability as well as biocompatible performance in terms of mechanical intactness, low platelet adhesion, and being free of cytotoxicity [ 20 ]. We also observed that the mechanical property of blends of sulfonated PP/ tert -butyl SEPS with different mixing ratios was brittle, and the brittleness of blends of sulfonated PP/ tert -butyl SEPS film can be reduced dramatically with the aid of mineral oil as an additional plasticizer.…”
Section: Introductionmentioning
confidence: 99%